PARTISIPASI ELEMEN MASYARAKAT FILM TERHADAP PERSOALAN LINGKUNGAN HIDUP - Yanuar Luqman; Muhammad Wahyu Widagdo; Nurist Surayya Ulfa (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2022)
Environmental issues are very complex things that require the participation of various elements of society. The film community is one element of society that is expected to contribute to participation in environmental management. The film produced by the community is one of the cultural artifacts, environmental communication is also inseparable from culture as its context. Film is also a participatory media that is used for the important role of community participation in creating special appropriate media content. With a qualitative descriptive method, this study aims to determine the strategy of the film community in conveying environmental messages. The results showed that the two selected communities had an equally important concern for environmental sustainability. Both use social media for communication coverage through films by choosing advocating narratives to provide a space for dialogue between the general public and interested parties, in this case the government and contributors to environmental problems.